Penerapan Besaran dan Satuan Dalam Kehidupan - Mufidha, Tiara Aulia; Oktaviani, Ferra Dian; Kelen, Redemptus Pulo; Lestari, Yunita; Kurniawati, Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of making this article is to understand the importance of understanding the concept of measuring quantities and units so that we can do things correctly and according to size. A unit is a unit used to measure magnitude. Units are used to measure quantities in precise quantities. While magnitude is everything that can be measured, calculated, expressed by numbers, has values and units. Learning innovation is needed to increase understanding of the concept of measuring quantities and units in everyday life. So that it can be applied in everyday life.